Cognitive deficits and psychosocial functioning in adult ADHD: Bridging the gap between objective test measures and subjective reports. Issue 6 (2nd July 2020) - Kallweit, Claudia; Paucke, Madlen; Strauß, Maria; Exner, Cornelia
ABSTRACT: Introduction: Self-reported cognitive deficits in adult Attention-Deficit/Hyperactivity-Disorder (ADHD) are often not corroborated by standardized tests. Tests and reports also differ in their correspondence to aspects of psychosocial functioning. Executive function tasks (EF-tasks) using material close to daily life, may provide a more ecologically-valid assessment of cognitive deficits. Method: 36 adults with ADHD and 36 healthy controls performed standardized EF-tasks and corresponding EF-tasks using material close to daily life and gave self-reports on cognitive functioning. The study investigated performance differences and the predictive utility of cognitive measures for psychosocial functioning. Results: While all the self-reports showed substantial cognitive impairments for the ADHD group, this was only shown in some of task measures. For two domains, the deficits in EF-tasks with material close to daily life were similar or smaller than assessed with traditional measures. However, three tasks, which used material of daily life, revealed more deficits than the corresponding more standardized tasks. Beyond cognitive self-reports the new tasks did not contribute substantial to psychosocial functioning, similar to the standardized tasks. Conclusions: Tasks using material close to daily life have the potential to objectify reported everyday life deficits better than more standardized tests, at least in single EF-domains. When relevant methodical aspects of these tasks will be more targeted and considered systematically in future research, the tasks might contribute to assessments of psychosocial functioning. Then they could also be used as outcome measures in intervention studies.